2015
DOI: 10.1038/srep11605
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-sync: disrupted neural activity in emotional circuitry during film viewing in melancholic depression

Abstract: While a rich body of research in controlled experiments has established changes in the neural circuitry of emotion in major depressive disorders, little is known as to how such alterations might translate into complex, naturalistic settings - namely involving dynamic multimodal stimuli with rich contexts, such as those provided by films. Neuroimaging paradigms employing dynamic natural stimuli alleviate the anxiety often associated with complex tasks and eschew the need for laboratory-style abstractions, hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 52 publications
(71 reference statements)
6
55
2
Order By: Relevance
“…Although in a preliminary study of Quinn et al (2012) and in the study of Guo et al (2015), no significant differences were found for the melancholic, non-melancholic and control groups for gender or age, the difference compared to our findings may be due to their focus on the adult population in addition to a smaller sample size that decreases the chances of finding significant difference.…”
Section: Discussioncontrasting
confidence: 99%
“…Although in a preliminary study of Quinn et al (2012) and in the study of Guo et al (2015), no significant differences were found for the melancholic, non-melancholic and control groups for gender or age, the difference compared to our findings may be due to their focus on the adult population in addition to a smaller sample size that decreases the chances of finding significant difference.…”
Section: Discussioncontrasting
confidence: 99%
“…In an fMRI study at the other end of the developmental spectrum (ages 18-88 years), networkbased ISCs during movie-watching were found to decrease with advancing age (Campbell et al, 2015). In psychiatric populations, adults with autism spectrum disorder exhibited higher ISCs of BOLD-signal time-courses during movie-watching relative to healthy controls (Hasson et al, 2009;Salmi et al, 2013), and similar patterns have been found in individuals with schizophrenia when watching humorous movie clips (Tu et al, 2019) and in major depressive disorder across positive, negative and neutral clips (Guo et al, 2015). Overall, these longer time-course analyses (ISCs) suggest that neural variability across participants is higher when the brain is immature or during advanced aging, as well as when individuals have psychiatric disorders.…”
Section: Connectome Stability and Similarity As Developmental Measuresmentioning
confidence: 52%
“…In challenging populations such as children or cognitively impaired patients, naturalistic paradigms could greatly alleviate anxiety related to in‐scanner performance as well as head motion [Vanderwal et al, ]. A series of innovative studies have recently revealed altered brain dynamics and connectivity during natural movie viewing in autism, major depressive disorder, and altered states of consciousness [Guo et al, ; Hasson et al, ; Hyett et al, ; Naci et al, ]. Therefore, naturalistic paradigms could provide a promising condition for mapping connectivity changes in neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%